A Checklist of the Moths of Alaska - Ferris, Clifford D.; Kruse, James J.; Lafontaine, J. Donald; Philip, Kenelm W.; Schmidt, B. Christian; Sikes, Derek S. (Zootaxa, 2012)
This article represents the first published complete checklist of the moth taxa, resident and occasional, recorded to datefor Alaska. Seven-hundred and ten species are listed. General species distribution ranges within the state are included.Three North American records are listed for the first time: Cydia cornucopiae (Tengström); Eucosma hohenwartiana ([D. & S.]); Acronicta menyanthidis (Vieweg).